PTU-206 Stent expulsion in diagnostic ERCP. (28th May 2012) - Nicholson, J; Amin-Nejad, A; Harrison, S; Greenhalf, W; Sutton, R; Neoptolemos, J; Sarkar, S; Smart, H; Evans, J; Lombard, M
Abstract : Introduction: Patients who have a high risk of developing pancreatic cancer (FPC) may have pre-malignant molecular changes and have been enrolled in a EUROPAC Study to conduct diagnostic ERCP for the collection of pancreatic juice. 1 2 These otherwise healthy patients have been identified as a higher risk group for ERCP-induced pancreatitis. 3 To reduce the incidence of post-ERCP pancreatitis a self-expelling plastic stent is routinely inserted into the pancreatic duct after ERCP. Stents have been shown to reduce pancreatitis in small cohorts but previous spontaneous intraluminal migration has been quoted at 67% for pancreatic stents. 4 5 Methods: Prospective observational study of 24 patients who underwent ERCP and secretin stimulated collection of pancreatic juice as part of the EUROPAC study. No pancreatic or biliary disease was present. In all patients a plastic stent was inserted (3 cm 5 Fr Zimmon, Cook Medical © ) to avoid post-ERCP pancreatitis. Plain abdominal x-ray was requested at 6 weeks post-ERCP to assess expulsion of the stent. Complications were recorded. Results: Of the 24 participants 16 were female. Abdominal x-rays were obtained in all patients at a median of 6 weeks (5–12 weeks) post-ERCP. Stents were retained in 2 (8.3%) patients. Spontaneous stent self-expulsion rate was therefore 91.7%. There were no other compliations. Hyperamylaseaemia occurred in 2 (8.3%) patients—unrelated to stent retention. Prior to routine stent insertion pancreatitis occurred in seven patients (46%), thus we have shown a reduction in ERCP-induced pancreatitis (p=0.003). Conclusion: In the absence of pancreatic and biliary disease stents will self-expel by 12 weeks. We have also shown that the deployment of small pancreatic stents is safe and well tolerated. Comparison with ERCP performed prior to routine stent placement has shown a significant reduction in the rate of pancreatitis. Both retained stents were removed without complication by a standard OGD. Competing interests: None declared. References: 1. Greenhalf W, et al. Screening of high-risk families for pancreatic cancer. Pancreatology 2009;9 :215–22. 2. Grocock CJ, et al. Familial pancreatic cancer: a review and latest advances. Adv Med Sci 2007;52 :37–49. 3. Williams EJ, et al. Risk factors for complication following ERCP: results of a large scale, prospective, multicentre study. Endoscopy 2007;39 :793–801. 4. Singh P, et al. Does prophylactic pancreatic stent placement reduce the risk of post-ERCP acute pancreatitis? A meta-analysis of controlled trials. Gastrointest Endosc 2004;60 :544–50. 5. Chahal P, et al. Pancreatic stent prophylaxis of post endoscopic retrograde cholangiopancreatography pancreatitis: spontaneous migration rates and clinical outcomes. Minerva Gastroenterol Dietol 2007;53 :225–30.